Potato Consumption and Risk of Cardiovascular Mortality and Type 2 Diabetes After Myocardial Infarction: A Prospective Analysis in the Alpha Omega Cohort - Cruijsen, Esther; Indyk, Indira M.; Simon, Anne W. E.; Busstra, Maria C.; Geleijnse, Johanna M. (Frontiers in Nutrition, 2022)
Background: Higher potato intake, especially French fries, was unfavorably associated with cardiometabolic endpoints in population-based studies. Little is known about this in ischemic heart disease (IHD) patients. Objective: Total and boiled potatoes and French fries intake were examined in relation to cardiovascular (CVD) mortality, all-cause mortality and type 2 diabetes mellitus (T2DM) risk in Dutch post-myocardial infarction (MI) patients of the Alpha Omega Cohort. Methods: We analyzed 3,401 patients (60-80 y, 78% male), free from T2DM at baseline, with an MI ≤ 10 y before enrolment. Diet was assessed at baseline (2002-2006) using a 203-item validated food frequency questionnaire, including potato preparation methods. Cause specific mortality was monitored through December 2018 and T2DM incidence (self-reported physician diagnosis and/or prescribed anti-diabetes medication) was monitored during the first 40 months of follow-up. Multivariable Cox models were used to obtain Hazard Ratios (HRs) for fatal endpoints and incident T2DM in tertiles of potato intake. Results: Patients had a median total potato intake (mainly boiled) of 111 g/d, 96% consumed >1 serving (200 g) per week. French fries were consumed by 48% of the patients (median of 6 g/d among consumers). During >12 y of follow-up (38,987 person-years), 1,476 deaths occurred of which 641 from CVD, 394 from IHD and 119 from stroke. Total and boiled potatoes were not associated with CVD mortality, but a higher risk of all-cause mortality was observed (HR: 1.07; 95% CI: 1.01, 1.14; per 50 g/d). Potato consumption tended to be positively associated with incident T2DM (186 cases; HR: 1.11, 95% CI: 0.94, 1.32; per 50 g/d). Results for French fries were inconsistent for all outcomes. Conclusion: In Dutch post-MI patients, potatoes (mainly boiled) were not associated with CVD mortality, but possibly adversely associated with all-cause mortality and T2DM risk. These findings warrant confirmation in other IHD patient cohorts. The Alpha Omega Cohort is registered at Clinicaltrials.gov as NCT03192410.